Esthetic and Prosthetic Rehabilitation of Maxillary Lateral Incisor: A Case Report - Neetha J Shetty; Sweta Pradhan (Institute of Medico-legal Publications Pvt Ltd, 2022)
Introduction: The maxillary anterior region poses the highest number of aesthetic challenges in implant dentistryas any tooth loss in the region leads to bone resorption and collapse of gingival architecture leaving inadequatebone for implant placement. However, immediate implant placement and provisionalization has been a viableoption for replacing failing maxillary anterior teeth as it preserves the vertical existing osseous and gingivalarchitecture. A proper case selection guided by an appropriate step-by-step treatment plan can ensure the successof any immediate implant placement.Case Summary: This case report describes atraumatic extraction of a fractured right maxillary lateral incisor,followed by immediate placement of a dental implant in the prepared socket. Implant was successfully loaded andwas functional during 24 months follow up period. The patient exhibited no clinical or radiologic complicationspost operatively. Recall visits exhibited patient’s high-level confidence of smile with optimum satisfaction andsuccessful aesthetic outcome.Conclusion: Immediate implant placement into fresh extraction socket reduces the treatment time, cost, preservesthe gingival aesthetic and increases the comfort of the patient.